THE RELATION OF EMOTIONAL REGULATION WITH INTENSITY OF MENSTRUAL PAIN (DYSMENORRHEA) IN STUDENTS OF SMPN 8 PONTIANAK - Nanda Eka Putri (Jurnal Nasional Ilmu Kesehatan, 2020)
Dysmenorrhea is abdominal pain that originates from uterine cramps and occurs during menstruation. This dysmenorrhea generally occurs around 2 or 3 years after the first menstruation and reaches its climax when women are 15-25 years old. Dysmenorrhea can decrease psychosocial development, cognitive in adolescents, the influence of body image and female sexual identity. The purpose of this study is to know the relation between emotional regulation and menstrual pain (dysmenorrhea) in student of SMPN 8 Pontianak. This type of research is an observational analytic research with a cross-sectional research design approach. The number of samples is 73 people. The independent variables in this study was emotional regulation while the dependent variable in this study was menstrual pain (dysmenorrhea). The results is respondents who experienced mild dysmenorrhea were 49.3%, moderate dysmenorrhea were 31.5%, and severe dysmenorrhea were 19.2%. Respondents who experienced good emotional regulation were 79.5%, while those who experienced bad emotion regulation were 20.5%. . Based on the statistical test that had been done, there was a significant relation in both variables with p<0,05. The conclusion is there is a relation between emotional regulation and intensity of menstrual pain (dysmenorrhea) in students of SMPN 8 Pontianak.Keywords : dysmenorrhea, emotion regulation, students